2011
DOI: 10.1002/jbm.a.33127
|View full text |Cite
|
Sign up to set email alerts
|

A novel strontium‐doped calcium polyphosphate/erythromycin/poly(vinyl alcohol) composite for bone tissue engineering

Abstract: It is our goal to develop bactericidal bone scaffolds with osteointegration potential. In this study, poly(vinyl alcohol) (PVA) coating (7%) was applied to an erythromycin (EM)-impregnated strontium-doped calcium polyphosphate (SCPP) scaffold using a simple slurry dipping method. MicroCT analysis showed that PVA coating reduced the average pore size and the percentage of pore interconnectivity to some extent. Compressive strength tests confirmed that the PVA coating significantly increased material elasticity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 62 publications
(168 reference statements)
0
27
0
Order By: Relevance
“…PVA is a water-soluble polymer that can firstly swell and then partly dissolve in water solution. Our in vitro study 7 revealed that SCPP EM -PVA composite scaffolds significantly reduced the EM burst release and extended the EM release time up to 150 h. EM released from SCPP EM -PVA composites maintained its capability of bacterial growth inhibition. PVA coating also increases the mechanical strength and reduces the material fragility.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…PVA is a water-soluble polymer that can firstly swell and then partly dissolve in water solution. Our in vitro study 7 revealed that SCPP EM -PVA composite scaffolds significantly reduced the EM burst release and extended the EM release time up to 150 h. EM released from SCPP EM -PVA composites maintained its capability of bacterial growth inhibition. PVA coating also increases the mechanical strength and reduces the material fragility.…”
Section: Discussionmentioning
confidence: 82%
“…We previously showed that SCPP scaffold with PVA coating extended the impregnated erythromycin (EM) release in vitro. 7 In this animal study, we found that the pouch infection was eliminated by the host immune surveillance in the absence of SCPP scaffolds. In the presence of SCPP scaffolds, both the pouch tissues and scaffolds were infected.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations